Application of Linear Goals Programming Optimization Models in Determining The Optimal Configuration of Land Use at The Upper Citarum Watershed - Omo Rusdiana; R. Rodlyan Ghufrona (Departemen Silvikultur, Fakultas Kehutanan dan Lingkungan, Institut Pertanian Bogor (IPB), 2011)
Various natural disasters such as floods and landslides that much happening at this time caused by environmental damage, esppecially upper watershed damage. Actual land use of forests in the Upper Citarum Watershed area is only 16.20%, still not meet the minimum area of forest (30%) base on UU No. 41/1999 about Forestry. Actual land use configuration in study site causes most of the region is dominated by the level of erosion hazard very heavy; total RTH covering 76.75% total study site; and approximately 58.25% of farmer households unable to meet minimum standards for decent living needs. By applying a multiple target linear optimization model Linear Goals Programming (LGP) that solved by General Algebraic Modeling System (GAMS) optimization software, recommended the optimal configuration of land use that can meet the ecological and economic objectives. These recommendations can decrease the erosion rate of 94.13% and reaching 72.97% areas that meet standards of TSL; reaching an area covering 87.39% of RTH; and increasing aggregate sector of food crops, plantations, and forestry farm household income amount 220.83%. Optimization model in this study are static models that do not pay attention to time, but this models produces marginal values and we can analyze the value of elasticity (Sensitivity Analysis) that can be known implications for optimization purposes in case of changes in conditions of objective optimization.